Novel features of telomere biology revealed by the absence of telomeric DNA methylation - Vega-Vaquero, Alejandro; Bonora, Giancarlo; Morselli, Marco; Vaquero-Sedas, María I.; Rubbi, Liudmilla; Pellegrini, Matteo; Vega-Palas, Miguel A. (Genome Research, 2016)
Cytosine methylation regulates the length and stability of telomeres, which can affect a wide variety of biological features, including cell differentiation, development, or illness. Although it is well established that subtelomeric regions are methylated, the presence of methylated cytosines at telomeres has remained controversial. Here, we have analyzed multiple bisulfite sequencing studies to address the methylation status of Arabidopsis thaliana telomeres. We found that the levels of estimated telomeric DNA methylation varied among studies. Interestingly, we estimated higher levels of telomeric DNA methylation in studies that produced C-rich telomeric strands with lower efficiency. However, these high methylation estimates arose due to experimental limitations of the bisulfite technique. We found a similar phenomenon for mitochondrial DNA: The levels of mitochondrial DNA methylation detected were higher in experiments with lower mitochondrial read production efficiencies. Based on experiments with high telomeric C-rich strand production efficiencies, we concluded that Arabidopsis telomeres are not methylated, which was confirmed by methylation-dependent restriction enzyme analyses. Thus, our studies indicate that telomeres are refractory to de novo DNA methylation by the RNA-directed DNA methylation machinery. This result, together with previously reported data, reveals that subtelomeric DNA methylation controls the homeostasis of telomere length.
10.1101/gr.202465.115